Barkitov limfom kao uzrok intususcepcije – Važnost pozitronske emisione tomografije za praćenje bolesti - Radovanović, Zoran; Slavković, Andjelka; Marjanović, Zoran; Živanović, Dragoljub; Djordjević, Ivona (Vojnosanitetski pregled, 2017)
Introduction. Burkitt lymphoma (BL) is a high-grade, high-risk type of non-Hodgkin lymphoma characterized by a very rapid cell progression. Although BL is a rare cause of intussusceptions, it must arouse suspicion if the intussusception occurs outside the characteristic peak. Case report. A previously healthy 7-year-old boy was hospitalized for recurrent abdominal pain, loss of appetite and body weight, a fever of up to 38°C, persistent vomiting and with soft tumefaction ileocecally. Nuclear magnetic resonance (NMR) revealed intussusceptions due to a tumor mass, which was followed by a surgical procedure (right hemicolectomy and termino-terminal anastomosis). Histopathological examination confirmed the diagnosis of primary abdominal Burkitt lymphoma. In spite of the subsequent oncologic treatment lasting for four months, an undifferentiated mass was detected in the retroperitoneal space below the lower pole of the right kidney. Positron emission tomography (PET) scan was performed in order to detect the metabolic activity of the deposit in the retroperitoneal space. A high metabolic activity of Burkitt lymphoma confirmed its presence, as well as the need for additional surgical intervention for tumor extirpation. PET scan undoubtedly contributed to distinguishing the visibility of tumor cells and to the detection of the subcentimeter tumor mass. Conclusion. The timely diagnosis, high tumor sensitivity to chemotherapy as well as the great importance of PET scan in the early detection of tumor recurrence, significantly increase the survival rate in patients with BL.